Frequency of Pseudomonas spp. Fluorescent Groups From Different Health Centers in Nueva Esparta State-Venezuela - O Mago; J Betancourt; E Castillo; G González; G Marín (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
Nonfermentative Gram-negative Bacilli (NFGNB) are clinically a group of important bacteria due to their evident pathogenisis. With the objective of determining the frequency of the gender Pseudomonas, 206 samples of NFGNB from patients were evaluated at one of the main public health centers in Nueva Esparta state: the Central Porlamar Hospital , an Ambulatorio tipo III hospital in Salamanca (Asunción) and ae type 1Hospitalo Juan Griego, during the period between January and April 2002. Of the total analyzed samples, 141 (68,4%) corresponded to the main species of the fluorescent group of the gender Pseudomonas and the 65 remaining samples (31,6%) corresponded to other NFGNB. Pseudomonas aeruginosa was the most frequent with 97,9%, followed by P. fluorescens (1,4%) and P. putida (0,7%). Of the different types of samples studied, it was found that the secretion of wounds from lesions in inferior members was the most frequent, in which the most frequent isolate species was P. aeruginosa, with 93,9%. Also, the highest percentage in isolates from the florescent group species occurred in the Intensive Care Unit (UTI) in the Porlamae Hospital.